2022
DOI: 10.1097/gox.0000000000004424
|View full text |Cite
|
Sign up to set email alerts
|

Echo-guided Lower-back Sculpture and Volumization as a Complement to High-definition Liposuction (XPINE-FAT)

Abstract: Background: Knowledge about lower-back aesthetics is very limited, especially regarding surgical techniques that improve its appearance. Thus, this study aimed to describe a high-definition liposuction technique with intramuscular grafting of erector spinae muscles (longissimus). Methods: A total of 15 female patients 25-48 years of age were recruited between November 2021 and January 2022, who underwent body contouring surgery and subsequently underwent a low-back lipodefinition and echo-guided intramuscular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 29 publications
(78 reference statements)
0
17
0
Order By: Relevance
“…Our approach to the Hv-FAT procedure involves regarding the gluteal region as a box and the lower back as the upper frame. For these regions, several types of treatments are currently available, including the XPINE-FAT technique of fat grafting on erector spinae muscles, PRS Global Open • 2023 6 using intraoperative ultrasound, 12 thereby improving the transition from the lower back to the gluteal region. For the profile view, which is determined by the hips, liposuction or fat transfer can be used based on the requirements of each patient.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our approach to the Hv-FAT procedure involves regarding the gluteal region as a box and the lower back as the upper frame. For these regions, several types of treatments are currently available, including the XPINE-FAT technique of fat grafting on erector spinae muscles, PRS Global Open • 2023 6 using intraoperative ultrasound, 12 thereby improving the transition from the lower back to the gluteal region. For the profile view, which is determined by the hips, liposuction or fat transfer can be used based on the requirements of each patient.…”
Section: Discussionmentioning
confidence: 99%
“…Fat grafting is being increasingly used to volumize muscle groups, especially as a complement to body contouring surgery, styling, and highlighting with liposuction results and few adverse events. [8][9][10][11][12][13][18][19][20][21] The results showed that the increase of the thickness in the immediate postoperative period is evident and 1-month follow-up ultrasound measurements highlighted a decrease in the muscle thickness in relation to the immediate postoperative period in all fat-grafted muscle groups (long head of the biceps femoris and semitendinosus muscles), bilaterally. Nevertheless, despite these results, the patients maintained a good distribution of muscle thickness 1 month after surgery, and this decrease is minimal when compared with the thickness initially obtained after fat grafting, which suggest that the results are possibly sustainable over time (Table 4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of US deepens basic understanding of anatomy and helps to reveal individual differences and further tailor techniques. [14][15] US enables us to further personalize the areas to highlight while respecting each patients' individual characteristics. [16][17][18] US is an easy way to improve the marking technique for liposuction of the rectus abdominis or other surgical interventions on the anterior wall of the abdomen in clinical practice.…”
Section: Discussionmentioning
confidence: 99%